HbA1c as indicator for dyslipidaemia, cardiovascular and atherosclerotic events in patients with metabolic syndrome - Alyasiri, Haider (University of Thi-Qar Journal of Science, 2015)
HbA1c is well known indicator for control of DM. We try in this study to discuss the relationshipbetween HbA1c level and some atherosclerotic events and S. lipid abnormalities in patients with metabolic syndrome.Patients and methods: 226pts involved in this study. Metabolic syndrome was assessed according to the US National Cholesterol Education Program Adult Treatment Panel III (2001) that was modified at 2004 , cross-sectional study performed in diabetes and endocrine center between 2008-2011. Parameters like Sex, races, age, job, residency, smoking had been taken into consideration , HbA1c was measured by immunoturbidimetric assay with a Cobra Integra 800 automatic analyzer (Roche Diagnostics, Basel, Switzerland) with a reference value of 4.4–6.0%. Conclusion: close relationship was found between HbA1c and hypertension, s.cholestrol, s. triglyceride, HDL, s.VLDL, and LDL and Increasing level of HbA1c was associated with increasing level of s. lipids, cardiovascular riskfactors and severity of metabolic syndrome.